2023
DOI: 10.1177/11206721231156493
|View full text |Cite
|
Sign up to set email alerts
|

Progression of bilateral morning glory syndrome associated with unilateral persistent fetal vasculture: A case report of long term follow-up in an infant

Abstract: Purpose To describe a case of Bilateral Morning Glory Syndrome (MGS) associated with Unilateral Persistent Fetal Vasculature (PFV) in a 3-day old neonate. Observations A 3-day-old neonate was found bilateral retinal abnormalities due to neonatal eye screening. Dilated fundus exam showed bilateral optic disc dysplasia with the persistent hyaloid vessels in right eye at first. With the progress of the disease, optic disc was enlarged with central umbilication which with a similar anomalous radiating peripapillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Morning glory syndrome (MGS) is a rare congenital optic disc abnormity, which was named by Kindler in 1970, characterized by an enlarged optic disc with deep excavation and peripapillary pigmentation, a central glial tuft and radial retinal vessels 1 . It has been reported that the pathogenesis of MGS is associated with the maldevelopment of the lamina cribrosa and posterior sclera 2,3 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Morning glory syndrome (MGS) is a rare congenital optic disc abnormity, which was named by Kindler in 1970, characterized by an enlarged optic disc with deep excavation and peripapillary pigmentation, a central glial tuft and radial retinal vessels 1 . It has been reported that the pathogenesis of MGS is associated with the maldevelopment of the lamina cribrosa and posterior sclera 2,3 …”
Section: Figurementioning
confidence: 99%
“…1 It has been reported that the pathogenesis of MGS is associated with the maldevelopment of the lamina cribrosa and posterior sclera. 2,3 Persistent hyperplastic primary vitreous (PHPV) is caused by the failure of regression of embryological primary vitreous and hyaloid vasculature. 4 Its characteristic is retrolental fibrovascular tissue, microphthalmia, retinal fold, intraocular hemorrhage, and lenticular opacification.…”
mentioning
confidence: 99%